Pendidikan Kejuruan Tata Busana Sebagai Katalisator Kewirausahaan Di BLK Pesantren - M.Khoirul Muttaqin; Nursamsi Nursamsi (STIKes Ibnu Sina Ajibarang, 2023)
This study aims to find solutions related to students' low interest in developing entrepreneurship. In fact, currently there are many fashion vocational education as entrepreneurs in Islamic boarding schools. Many government assistance such as sewing machines and other training rooms are disbursed in the assistance scheme for BLK Islamic Boarding Schools. Today's students are required not only to delve into religious knowledge but also to be able to be entrepreneurial. The existence of BLK is expected to improve the skills of students in the field of fashion design. However, the existence of a job training center and a number of sewing machine assets has not been optimized, especially to produce products that can be commercialized. The solutions offered are in the form of entrepreneurship training and veil making training as an effort to optimize and commercialize the assets of the Job Training Center that have been owned.